Reducing feather pecking and cloacal cannibalism by providing layer breeders with nest boxes in colony cages for natural mating - Shi, Haipeng; Zheng, Weichao; Tu, Jiang; Li, Baoming (International Journal of Agricultural and Biological Engineering, 2018)
Colony cages for natural mating have been applied on many layer breeder farms. However, feather pecking and cloacal cannibalism are considered as prominent problems for these systems. This study aimed to investigate the effects on feather pecking and vent pecking behaviors by providing layer breeders with nest boxes (0.90 m L × 0.40 m W × 0.60 m H) in colony cages for natural mating (4.80 m L × 1.20 m W × 0.71 m H). Video recording and artificial observation were adopted. The results showed that the usage of nest boxes gradually increased from the beginning of nest boxes providing at the age of 37 weeks to the end of the experiment at the age of 55 weeks. The utilization rates of nest boxes were 36.75%, 44.75% and 50.38% at the ages of 41 weeks, 47 weeks and 53 weeks, respectively. The hens in the cages without nest boxes showed significantly more frequent gentle feather pecks (both given and received) than hens in the cages with nest boxes at the ages of 41 weeks, 47 weeks and 53 weeks. A decreasing trend of gentle feather pecking frequency (both given and received) was found with the increasing age for both the two groups. No significant difference was found in the number of given or received severe feather pecks at the age of 41 weeks. The hens in the cages without nest boxes showed a significantly higher frequency of given and received severe feather pecks than hens in the cages with nest boxes at the ages of 47 weeks and 53 weeks (p<0.05). Both cannibalistic injury occurrence and mortality rate in the cages with nest boxes were significantly lower than those in the cages without nest boxes. In conclusion, providing nest boxes in colony cages for natural mating could decrease abnormal pecking behaviors and improve animal welfare conditions of layer breeders. Keywords: feather pecking, vent pecking, nest box, colony cage, cloacal cannibalism, layer breeder, animal welfare DOI: 10.25165/j.ijabe.20181106.3323 Citation: Shi H P, Zheng W C, Tu J, Li B M. Reducing feather pecking and cloacal cannibalism by providing layer breeders with nest boxes in colony cages for natural mating. Int J Agric & Biol Eng, 2018; 11(6): 27–32.